MANAJEMEN KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Yuni lestari Yuni; Ahmad Thohirin; Suyitno (STKIP Subang, 2025)
Teacher performance is one of the key factors in improving the quality of education in schools. The principal, as an educational leader, has a strategic role in managing and directing school resources, especially teachers, to perform professionally and optimally. This article aims to examine the influence of principals’ leadership management on teacher performance through a literature review approach. The method used is a literature study by analyzing various scientific sources, including books, journal articles, and relevant previous research related to educational leadership and teacher performance. The results of the review indicate that effective principal leadership management, which includes planning, organizing, implementing, and supervising, as well as the application of democratic and visionary leadership styles, has a positive impact on improving teacher performance. Principals who are able to provide motivation, guidance, and create a conducive working environment can encourage teachers to enhance their competence, discipline, and professional responsibility. Therefore, principal leadership management is an important factor in improving teacher performance and ensuring sustainable educational quality.